Six-Pointed Star Motif in Muslim Architecture of Bangladesh (Past Bengal) and Turkish Influence: An Historical Study - Islam, Sk. Zohirul (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
With the rise of Islamic states as the dominant powers of India and Indian Sub- Continent (India, Pakistan and Bangladesh) and South Asia Sultanate and Mughal period (1200-1800 A.D.), by Turkish heroic figure (horsemen), Indian art was subjected to Islamic influence, resulting in a hybrid aesthetics as well as Indo- Islamic art which flourished to varying extends across south and southeast Asia. Bangladesh is world third largest Muslim majority country and situated in South Asia. So the main and primary identity of the notion is mosque architecture and then languages via culture in Bangladesh (past Bengal). Moreover, Traditional history called Mughal and ottoman was the center of all traders and referred as the “Middle Man” due to access to water routes between Asia and Europe. The Ottoman and Mughal Empires were all founded with art and architecture by members of the same ethnically Turkic tribe and originated from Oghuz tribe. Firstly, in the early 14th century, Osman Bey established a small principality in the northeast corner of Anatolia. Despite these many similarities, there are some key difference within the approach to Islamic Art and Architecture from Miniatures Illustrations in Indian Sub-Continent to Mosque architecture in Turkey and the Levant the Mughal and Ottoman empires left their indications.Turkish Military Ikhtiyar Uddin bin Muhammad Bhaktiyer Khilji and his Turkish followers captured Bengal in 1204 A.D. and after then ruled by Turkic. Besides these many Sufis saint-like Khan Jahan Ulugh Khan, Burhan Khan, Gharib Shah, came here and spread Islam and Turkish culture with languages too. The Ilyas Shahi dynasty was the first independent Turkic Muslim ruling dynasty in late medieval Bengal, which ruled from the 14th century to the 15th century. It was founded in 1342 by Shamsuddin Iliyas Shah. As follows still presence many Turkish words which used in the Bengali language as Barood, Nishan, Chaku, Bahadur, Begum, Chadar, Surma, bavarchi, kiyma, Korma, and so on. And then showed their power through art and architecture as Mosques and Tombs follows Adina Masjid at Pandua in 1368 A.D.; Eklakhi mausoleum, Pandua; Tomb of Shah Rukn-e Alam in Multan, Sixty Domed Mosque at Bagherhat of Bangladesh, etc. Based on all evidence present, it can be found that the Turks contributed significantly to Bengali languages and culture as well as art and architecture (Mosques and Tombs). Besides many Jewish people came in here through missionary and business purposes. And also we see that there have been found many designs in mosque architecture especially six-point stars which is mentioned as a David symbol. So my focus is the Connectivity between Turkish and Bangladesh through Islamic architecture and Jewish with six point star/hexagon/seal of Solomon. It is a historical study with a journalistic approach.